Visualization of water accumulation in micro porous layers in polymer electrolyte membrane fuel cells using synchrotron phase contrast tomography. (December 2022) - Alrwashdeh, Saad S.; Al-Falahat, Ala'a M.; Markötter, Henning; Manke, Ingo
Abstract: Using phase-contracted synchrotron X-ray tomography, this study investigates the water distribution within the microporous layer (MPL) of polymer electrolyte membrane fuel cells (PEMFCs). Synchrotron X-ray tomography used to analyze the water distribution in the whole gas diffusion medium (GDM), which comprises the microporous layer (MPL) and the gas diffusion layer (GDL). The MPL has already been identified. In the future, the development of GDMs could be employed to enhance the performance and operating conditions of PEMFCs.